2014 Fourth International Workshop on Domain-Specific Languages and High-Level Frameworks for High Performance Computing 2014
DOI: 10.1109/wolfhpc.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

The OPS Domain Specific Abstraction for Multi-block Structured Grid Computations

Abstract: Code maintainability, performance portability and future proofing are some of the key challenges in this era of rapid change in High Performance Computing. Domain Specific Languages and Active Libraries address these challenges by focusing on a single application domain and providing a high-level programming approach, and then subsequently using domain knowledge to deliver high performance on various hardware.In this paper, we introduce the OPS high-level abstraction and active library aimed at multi-block str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 20 publications
(21 reference statements)
0
57
0
Order By: Relevance
“…Some have proposed the use of domain-specific languages (DSLs), providing a limited set of high-level abstractions for a specific domain alongside a mechanism for generating optimized platform-specific binaries (e.g. Liszt [7], OP2 [19], [25], [26], STELLA [10], Pochoir [31], PATUS [5], Halide [24] and Nabla [4]). Others have proposed portability frameworks that take a different approach, providing a lower-level abstraction of performance-enabling hardware for developers to program against: some of these tools are truly languages or language extensions (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Some have proposed the use of domain-specific languages (DSLs), providing a limited set of high-level abstractions for a specific domain alongside a mechanism for generating optimized platform-specific binaries (e.g. Liszt [7], OP2 [19], [25], [26], STELLA [10], Pochoir [31], PATUS [5], Halide [24] and Nabla [4]). Others have proposed portability frameworks that take a different approach, providing a lower-level abstraction of performance-enabling hardware for developers to program against: some of these tools are truly languages or language extensions (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Herdman et al performed a similar analysis to the one presented in this research, evaluating OpenACC, OpenCL, and CUDA using a sister mini app of Tealeaf's, CloverLeaf. CloverLeaf has also been used to investigate the performance of the OPS DSL …”
Section: Related Workmentioning
confidence: 99%
“…CloverLeaf has also been used to investigate the performance of the OPS DSL. 26,27 Rupp et al 28 CPU with respect to microscopy image analysis. They concluded that the devices had a significant variance between particular operations, exposing some preference for particular operations.…”
Section: Related Workmentioning
confidence: 99%
“…The OPS (Oxford Parallel library for Structured meshes) DSL (Domain Specific Language) [9], [10] is essentially a C/C++/Fortran domain-specific API that uses source-tosource translation and various back-end libraries to automatically parallelise applications. Any code written using arXiv:1704.00693v2 [cs.PF] 26 Jun 2017 its API can utilise MPI, use multi-core CPUs with OpenMP, as well as GPUs with CUDA, OpenACC, or OpenCL.…”
Section: Introductionmentioning
confidence: 99%